Regulatory role of free fatty acids in maintain of membrane homeostasis in heart mitochondria at experimental myocardial ischaemia - M. V. Egorova; S. A. Afanasiyev (Бюллетень сибирской медицины)
The rate of oxygen uptake by heart mitochondria (Mch) at different heart pathologies (myocardial infarction, diabetes mellitus and their combination) was studied polarographically. The rate of oxygen uptake of damaged heart Mch and content of free fatty acids (FFA) were increased. Change of these parameters was increased with the development of pathologies that is most pronounced in the groups «diabetes» and «diabetes + myocardial infarction». In the group of «myocardial infarction + diabetes» pathological process was developed less intensively in comparison with individual pathologies. Addition of FFA suppressed the rate of oxygen uptake of Mch. Equally, inhibition of phospholipase A2 suppressed the respiration of Mch. The hypothesis that FFA act as modulators of the activity of phospholipase A2 was discussed.